2018
DOI: 10.21859/jech.5.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy: An Effective Component to Overcome Perceived Barriers to Adoption of Preventive Behaviors in the Health Belief Model

Abstract: Dear Editor-in-Chief:Health Belief Model is one of the most widely used models in health behaviors and it is considered an individual model of behavioral study. This model measures the relationship between health belief and health behavior, and it is based on the hypothesis that the adoption of preventive behavior is based on the beliefs of the person. In this model, whatever perceived susceptibility, perceived severity, and perceived benefits are stronger, perceived barriers are weaker, and the probability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Another reason for decreasing the score of perceived barriers in the test group in this study could be to increase self-efficacy because self-efficacy affects perceived barriers and higher self-efficacy reduces perceived barriers in performing the behavior [ 41 ]. The HL could also be effective in reducing perceived barriers by creating sufficient awareness and increasing perceived sensitivity, perceived intensity, perceived benefits, and self-efficacy [ 42 ]. This result was consistent with the results of studies by Jeihooni Khani et al [ 28 ] and Karimi Aval et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for decreasing the score of perceived barriers in the test group in this study could be to increase self-efficacy because self-efficacy affects perceived barriers and higher self-efficacy reduces perceived barriers in performing the behavior [ 41 ]. The HL could also be effective in reducing perceived barriers by creating sufficient awareness and increasing perceived sensitivity, perceived intensity, perceived benefits, and self-efficacy [ 42 ]. This result was consistent with the results of studies by Jeihooni Khani et al [ 28 ] and Karimi Aval et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing self-efficacy of the intervention group in this study could be due to increasing the level of HL because increasing HL has a positive effect on improving self-efficacy [ 10 , 43 ]. Other possible reasons for self-efficacy increment could be perceived barrier reduction [ 42 ] and awareness increment. This result was in line with the results of studies by Karimi Aval et al [ 38 ], Jeihooni et al [ 28 ], and Torbaghan et al [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is not just an individual responsibility. The health system and related sectors must provide the necessary facilities to promote health literacy on a larger scale and for a larger segment of the community [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the components of the HBM, perceived barriers have been cited as the most significant predictor of behaviour change. 244,245 Common examples of these perceived barriers to regular physical activity and practicing healthy eating habits are the absence of exercise facilities, finding time to exercise, willpower, and the cost of healthy food. 246,247 Various studies have reported on the barriers to healthy lifestyles experienced by workers as reported in a systematic review by Mazzola.…”
Section: Introductionmentioning
confidence: 99%